Slovenščina kot drugi/tuji jezik in slovensko jezikovno načrtovanje - Stabej, Marko (Jezik in slovstvo, 2004)
Slovene as a second/foreign language is an important component of the modern Slovene linguistic situation. Slovenia's independence and its integration with the European Union have resulted in the increasing presence of the Slovene language in the international setting, both in the institutional and non-institutional framework. An increasing number of people need or want to obtain active linguistic competence of Slovene as a foreign language. Language planning in the country has partly taken into account these processes and has offered some efficient solutions in the acquisition and assessement of linguistic competence. What remains open, however, are questions concerning the description and codification of the Slovene language, as well as those related to the consolidation of the status of Slovene as an official European language and the linguistic awarness of its speakers.
Keywords: sociolinguistics; sociolingvistika; jezikovna politika; jezikovno narčrtovanje; Slovene; slovenščina; slovenščina kot drugi ali tuji jezik